ANALISIS MODEL PRILAKU MBTI (MYERS BRIGGS TYPE INDICATOR), MOTIVASI KERJA DAN KEPUASAN KERJA PEGAWAI PADA KANTOR UNIT PERPUSTAKAAN BIOTEKNOLOGI - LIPI KABUPATEN BOGOR - Tutang .; Yuni Analita (Jurnal Ilmiah Binaniaga, 2008)
Employees are the main wealth of a company, because without their participation, the company’s activities will not occur. Employees play an avtive role in establishing plans, systems, processes and objectives to be achieved. One factor to improve the performance of the employees are motivated in motivating managers to stimulate subordinates by giving a gift to those who excel in the achievement standards, with the motivation of this spirit of working staff will increase because people generally happy to accept that just fine.    Analytical results obtained by calculating R = 0.842. from the comparison of calculated R = 0.842 is greater than table Z = +0.4496 then H0 is rejected. Means there is a significant relationship between motivation and the MBTI work together on employee job satisfaction at the Office of Library Unit in Biotechnology - LIPI Kabupaten Bogor. Based on the analysis above, partially proven that (a) motivation to work and a significant positive effect job satisfaction with t count value of 6.217 and 0.000, or 0% probability of below 5%, so the motivation to work to support the everyday work of employees on Library Unit Office of Biotechnology - LIPI Kabupaten Bogor. (b) the condition of MBTI and no significant negative effect on job satisfaction with t count value = -0.514 and 0.614 0r 61.4% probability of above 5% so that the MBTI is not able to support the everyday work of employees in the Office of Library Unit in Biotechnology - LIPI Kabupaten Bogor.